Association between self-reported sexually transmitted infection treatment and mental health symptoms in conflict-affected eastern Democratic Republic of the Congo. (March 2018) - Koegler, Erica; Kennedy, Caitlin E; Thompson, Carol B; Winch, Peter J; Mpanano, Remy M; Perrin, Nancy A; Glass, Nancy
Although poor mental health has been associated with sexual risk behavior, few studies have examined the association between mental health and sexually transmitted infections (STIs) in conflict-affected settings. With elevated symptoms of poor mental health in conflict-affected settings, it is important to consider if and how mental health may be a risk factor for STIs in these settings. We used cross-sectional logistic regression to examine the association between symptoms of depression, anxiety, and post-traumatic stress disorder (PTSD) with having been treated for an STI in rural South Kivu, Democratic Republic of the Congo. Among 753 adults, those with elevated self-reported symptoms of depression and anxiety (adjusted OR = 2.73, 95% CI 1.68, 4.44) and PTSD (adjusted OR = 1.89, 95% CI 1.17, 3.06) had higher odds of reporting ever being treated for an STI than those who were not symptomatic. Our findings suggest that future studies are needed to more rigorously examine the relationship between mental health and STIs.